Can Quantab titrator sticks reliably predict urinary sodium?. (February 2018) - Hamilton, Fergus W.; Penfold, Chris M.; Ness, Andrew R.; Stevenson, Kirsty P.; Atkinson, Charlotte; Day, Andrew M.; Sebepos-Rogers, Gregory M.; Tyrrell-Price, Jonathan
Summary: Background & aims: Urinary sodium concentration is a commonly used marker for extracellular fluid depletion which is often associated with dehydration. A point of care test for urinary sodium may reduce delays in clinical decision making by offering more timely guidance leading to improved salt and fluid management. We compared laboratory assessed urinary sodium with a potential point of care measure of urinary chloride in a variety of in- and outpatient specialities, to explore its use as an indicator of low urine sodium. Methods: Urinary chloride concentrations were estimated using a Quantab titrator stick in samples from patients that had been sent for urinary sodium assays. We validated the results of this titrator stick with laboratory-assessed sodium concentrations by deriving correlation coefficients between these methods and using limits of agreement testing. We determined the optimal titrator stick cut-point for identifying low urinary sodium (urinary sodium <20 mmol/L) by maximising the product of the sensitivity and specificity. This level of urinary sodium was used to mirror the British Society of Gastroenterology guidance on short bowel patients Nightingale and Woodward, 2006. Results: We obtained laboratory urinary sodium concentration and Quantab stick chloride measures on 127 samples. Twenty three percent had a urinary sodium below 20 mmol/L so were regarded as biochemically dehydrated. A threshold of <4.3 on the Quantab scale had a positive predictive value for low sodium of 56% (95%CI 40%–71%) and a negative predictive value of 94% (95%CI 87%–98%). Conclusions: These data suggest that the Quantab stick could be used as a point of care test to aid fluid and salt management decisions in an outpatient setting. Further work to explore the use of the titrator stick in specific patient populations at risk of salt and water depletion is justified.